ASEAN Decision-Making Process: Before and after the ASEAN Charter - Feraru, Atena S (Asian Development Policy Review, 2016)
The Association of Southeast Asian Nations (ASEAN) has long presented IR theorists with a paradox. This is due to the fact that it survived decades of intra-mural conflicts without having provided member states with any of the benefits that justify regional institutional arrangements in Europe. Current debate over the association’s effectiveness centers on ASEAN’s informal, strictly intergovernmental decision-making process, generally referred to as the ‘ASEAN Way’. Supporters credit it with having prevented intra-regional conflicts from escalating into open war by building confidence among member states; while critics regard endurance of this sovereignty-centered decision-making process as a fundamental obstacle to regional integration and emphasize the significant costs it entails. Notwithstanding widespread recognition of the essential role the ASEAN decision-making process plays in explaining regional cooperation, scholars seldom went beyond presenting the various formal and informal procedures, examining their consequences in relation to specific aspects of cooperation, or acknowledging their role in serving the interests of governments. The aim of this article is to provide an in-depth assessment of the evolution of regional decision-making actors and practices and examine the extent of the changes provided for by the ASEAN Charter. It looks at the role these practices play in achieving the objectives member governments set for the association, and finds that the basic policy-making cycle negotiated in late 1960s – early 1970s has been reinforced by subsequent institutional changes. The conclusion discusses implications of the continued relevance of this process to fulfilling ASEAN objectives.